Deepfake w świetle aktu w sprawie sztucznej inteligencji - Bień-Węgłowska, Iwona (PRAWO i WIĘŹ, 2025)
The Artificial Intelligence Act is the world's first regulation to establish a comprehensive legal framework specifying harmonized rules for the creation, use, and dissemination of AI systems. One of the areas regulated by the AI Act is deepfake technology, which encompasses AI systems that generate or modify synthetic content in the form of images, sounds, or videos that falsely appear authentic. This technology contributes to numerous abuses and is consistently associated with destructive behavior. EU legislators have recognized the risks associated with deepfake content – the Artificial Intelligence Act provides procedures to protect citizens from manipulation and disinformation, classifying deepfakes as limited risk and introducing transparency obligations for providers of AI systems that generate deepfake content, as well as for those who use them. The aim of this article is to provide a detailed analysis of the provisions of the Artificial Intelligence Act relating to deepfake technology, the scope of their application, and the method of enforcement. Additionally, the assessment will focus on the categorization of risks associated with deepfake content adopted by the EU legislator and its adequacy in the context of fundamental rights protection.